Myelin Damage in Diffuse Axonal Injury - Mu, Jiao; Li, Meiyu; Wang, Tingting; Li, Xiujuan; Bai, Meiling; Zhang, Guohui; Kong, Jiming (Frontiers in Neuroscience, 2019)
Diffuse axonal injury (DAI) is characterized by delayed axonal disconnection. Although the effect of DAI on axonal pathology has been well documented, there is limited information regarding the role of myelin in the pathogenesis of DAI. We used a modified Marmarou method to create a moderate DAI model in adult rat, and examined the corpus callosum and brain stem for myelin pathology and dynamic glial responses to DAI. During the first week following DAI, Luxol Fast Blue staining and western blot analysis for MBP showed significant loss of myelin in the corpus callosum and the brain stem. Increased apoptosis of mature oligodendrocyte, as depicted by its marker CC-1, was observed. Conversely, there was increased number of Olig2-positive cells accompanied by hypertrophic microglia/macrophage and mild reactive astrocytes. Electron microscopy revealed degenerating axons in corpus callosum and marked myelin abnormalities in brain stem in the early stage of DAI. Brain stem regions exhibit myelin intrusions or external protrusions with widespread delamination and myelin collapse, leading to degeneration of accompanying axons. Our results show distinct pathologic processes involving axon and myelin between the corpus callosum and the brain stem in DAI. Oligodendrocyte selective vulnerability and subsequent demyelination may contribute to axonal degeneration in brain stem. Defining the cause of ongoing oligodendrocyte death and promoting myelin regeneration may provide important targets for therapeutic interventions of DAI.